CARCINOMA MAMÁRIO EM TUMOR MISTO METASTÁTICO EM CÃO - Ferreira, Quênia Quécia de Sousa (2017)
Among the conditions observed in dogs and cats, the incidence of neoplasms of the mammary glands has increased due to the longer life expectancy of these animals. The purpose of this research is to describe a case of mammary carcinoma in a mixed tumor. A 5-year-old Perdigueiro female dog, 22 / kg, was brought to the veterinary hospital in Areia-PB. The owner reported presence of nodules in the mammary glands. Complete blood count and abdominal ultrasonography were requested for the patient. However, there were no changes. Therefore, the dog was submitted to the surgical procedure of bilateral radical mastectomy, the surgical specimen was sent to the Laboratory of Veterinary Pathology (LVP), and the histologic diagnosis was mammary carcinoma in a mixed tumor. After five months, the dog returned to the veterinary hospital with presence of new nodules, then additional examinations of hemogram and ultrasonography were requested. Relative eosinophilia was observed on the hemogram. In the ultrasonography exam were found changes in bladder, kidneys, abdominal cavity, spleen and liver. The bladder had a thin wall, anechoic content, bright echoes in suspension, and presence of rounded structure with echogenic capsule, hypoechoic content and anechoic areas. The kidneys had indefinite contours and loss of definition at the corticalmedullary junction and echotexture of the heterogeneous cortical parenchyma. The left kidney had areas of anechoic and hypoechoic circular contents (±1,36cm in diameter) in several areas of the renal parenchyma, and a hyperechoic focus was visualized in the renal cortex. The dog was euthanized and referred to the Laboratory of Veterinary Pathology (LVP), for necropsy. In the necropsy examination, nodules were observed in the spleen, pancreas, liver, bladder, kidneys, lungs, heart and oral cavity. In the evaluation of the histopathological examination, the dog was diagnosed with mammary carcinoma metastasis in a mixed tumor. In conclusion, the mammary carcinoma in a mixed tumor is very common in female dogs, as well as the development of metastases, which indicates an unfavorable prognosis and a greater difficulty in the treatment. A histopathological study is the definitive examination indicated for the diagnosis and classification of this neoplasm.